Effect of linkers with different chemical structures on photovoltaic performance of CdSe quantum dot-sensitized solar cells. (20th January 2021) - Zhang, Di; Zhang, Sidong; Fang, Yanyan; Xie, Dongmei; Zhou, Xiaowen; Lin, Yuan
Highlights: QDSCs were prepared by direct deposition of oil-soluble QDs based on TiO2 electrodes modified by three types linkers. Bifunctional linkers with different structures (phenyl-MBA, thiophene-TPA, and commonly used alkyl-TGA) have similar effect on cell performance. The MBA-TiO2 /CdSe QDSCs achieved the best efficiency of 5.50%. Abstract: Introducing bifunctional linkers (COOH-R-SH) between TiO2 electrodes and quantum dots (QDs) was an effective apprIntroducing bifunctional linkers (COOH-R-SH) between TiO2 electrodes and quantum dots (QDs) was an effective approach in preparation of quantum dot-sensitized solar cells (QDSCs). Three types of linkers (4-mercaptobenzoic acid (MBA, R =phenyl), 3-thiophenecarboxylic acid (TPA, R =thiophene), and thioglycolic acid (TGA, R =alkyl)) were used to functionalize TiO2 electrodes and prepare TiO2 /CdSe QDSCs with photoelectric conversion efficiency (PCE) of 5.50%, 4.59% and 4.85%, respectively. Various properties of modified and blank TiO2 electrodes, such as QDs loading, absorbance, work function, interfacial charge injection, recombination and their influence on PCE were investigated. In spite of low adsorption amounts of MBA on TiO2, the phenyl MBA-TiO2 electrodes obtained the highest Cd content due to regular arrangement and strong affinity to QDs. The FTIR spectra proved strong interactions between MBA and TiO2 electrodes, leading to fast electron injection from QDs to TiO2 electrodes. The electron injection rate in MBA-TiO2 electrodes was the same as blank-TiO2, larger than TGA- and TPA-ones. Work function of TiO2 electrodes modified by linkers could reduce several eV, in which the MBA-one decreased less, corresponding to the highest applied potential difference. The open-circuit voltage-decay measurement demonstrated that the MBA-TiO2 photoanodes had the least charge recombination. Enhanced light absorption capacity and fast electron injection rate were two key points for modified cell to improve short-circuit current, while low recombination and appropriate energy level positions increased open-circuit voltage. Those make MBA-TiO2 photoanodes obtain the best efficiency of 5.50%. We expected this work to guide the selection of linkers for design and optimization of photoanodes interface of QDSCs.oach in preparation of quantum dot-sensitized solar cells (QDSCs). Three types of linkers (4-mercaptobenzoic acid (MBA, R =phenyl), 3-thiophenecarboxylic acid (TPA, R =thiophene), and thioglycolic acid (TGA, R =alkyl)) were used to functionalize TiO2 electrodes and prepare TiO2 /CdSe QDSCs with photoelectric conversion efficiency (PCE) of 5.50%, 4.59% and 4.85%, respectively. Various properties of modified and blank TiO2 electrodes, such as QDs loading, absorbance, work function, interfacial charge injection, recombination and their influence on PCE were investigated. In spite of low adsorption amounts of MBA on TiO2, the phenyl MBA-TiO2 electrodes obtained the highest Cd content due to regular arrangement and strong affinity to QDs. The FTIR spectra proved strong interactions between MBA and TiO2 electrodes, leading to fast electron injection from QDs to TiO2 electrodes. The electron injection rate in MBA-TiO2 electrodes was the same as blank-TiO2, larger than TGA- and TPA-ones. Work function of TiO2 electrodes modified by linkers could reduce several eV, in which the MBA-one decreased less, corresponding to the highest applied potential difference. The open-circuit voltage-decay measurement demonstrated that the MBA-TiO2 photoanodes had the least charge recombination. Enhanced light absorption capacity and fast electron injection rate were two key points for modified cell to improve short-circuit current, while low recombination and appropriate energy level positions increased open-circuit voltage. Those make MBA-TiO2 photoanodes obtain the best efficiency of 5.50%. We expected this work to guide the selection of linkers for design and optimization of photoanodes interface of QDSCs.